Improved survival of patients with melanoma brain metastases in the era of targeted BRAF and immune checkpoint therapies. Issue 2 (12th October 2017) - Sloot, Sarah; Chen, Yian A.; Zhao, Xiuhua; Weber, Jamie L.; Benedict, Jacob J.; Mulé, James J.; Smalley, Keiran S.; Weber, Jeffrey S.; Zager, Jonathan S.; Forsyth, Peter A.; Sondak, Vernon K.; Gibney, Geoffrey T.
Abstract : BACKGROUND: The development of brain metastases is common for systemic treatment failure in patients with melanoma and has been associated with a poor prognosis. Recent advances with BRAF and immune checkpoint therapies have led to improved patient survival. Herein, the authors evaluated the risk of de novo brain metastases and survival among patients with melanoma brain metastases (MBM) since the introduction of more effective therapies. METHODS: Patients with unresectable AJCC stage III/IV melanoma who received first‐line systemic therapy at Moffitt Cancer Center between 2000 and 2012 were identified. Data were collected regarding patient characteristics, stage of disease, systemic therapies, MBM status/management, and overall survival (OS). The risk of de novo MBM was calculated using a generalized estimating equation model and survival comparisons were performed using Kaplan‐Meier and Cox proportional analyses. RESULTS: A total of 610 patients were included, 243 of whom were diagnosed with MBM (40%). Patients with MBM were younger, with a lower frequency of regional metastasis. No significant differences were noted with regard to sex, BRAF status, or therapeutic class. The risk of de novo MBM was found to be similar among patients treated with chemotherapy, biochemotherapy, BRAF‐targeted therapy, ipilimumab, and anti‐programmed cell death protein 1/programmed death‐ligand 1 regimens. The median OS of patients with MBM was significantly shorter when determined from the time of first regional/distant metastasis but not when determined from the time of first systemic therapy. The median OS from the time of MBM diagnosis was 7.5 months, 8.5 months, and 22.7 months, respectively, for patients diagnosed from 2000 to 2008, 2009 to 2010, and 2011 to the time of last follow‐up ( P  = .002). CONCLUSIONS: Brain metastases remain a common source of systemic treatment failure. The OS for patients with MBM has improved significantly. Further research into MBM prevention is needed. Cancer 2018;124:297‐305. © 2017 American Cancer Society . Abstract : Of 610 patients with unresectable stage III or IV melanoma who were treated with systemic therapy between 2000 and 2012, 243 patients (40%) were diagnosed with brain metastases. The median overall survival from the time of diagnosis of melanoma brain metastases has significantly improved since the introduction of newer therapeutic strategies (22.8 months for patients diagnosed between 2011‐present compared with 7.2 months and 8.4 months, respectively, for patients diagnosed before 2000‐2008 or 2009‐2010; P  = .002).